Population Genetic Difference of Pharmacogenomic VIP Variants in the Tibetan Population - He C; Peng L; Xing S; Li D; Wang L; Jin T (Dove Medical Press, 2021)
Chunjuan He,1 Linna Peng,1 Shishi Xing,1 Dandan Li,1 Li Wang,1 Tianbo Jin1,2 1Key Laboratory of Molecular Mechanism and Intervention Research for Plateau Diseases of Tibet Autonomous Region, School of Medicine, Xizang Minzu University, Xianyang, Shaanxi, 712082, People's Republic of China; 2Key Laboratory for Basic Life Science Research of Tibet Autonomous Region, Xizang Minzu University, Xianyang, Shaanxi, 712082, People's Republic of ChinaCorrespondence: Tianbo JinKey Laboratory of Molecular Mechanism and Intervention Research for Plateau Diseases of Tibet Autonomous Region, School of Medicine, Xizang Minzu University, #6, Wenhui East Road, Xianyang, 712082, Shaanxi, People's Republic of ChinaTel/Fax +86-29-88895902Email jintianbo@gmail.comBackground: Genetic variation influences drug reaction or adverse prognosis. The purpose of this research was to genotype very important pharmacogenetic (VIP) variants in the Tibetan population.Methods and Materials: Blood samples from 200 Tibetans were randomly collected and 59 VIP variants were genotyped, and then compared our data to 26 other populations in the 1000 project to further analyze and identify significant difference.Results: The results showed that on comparing with most of the 26 populations from the 1000 project, rs4291 (ACE), rs1051296 (SLC19A1) and rs1065852 (CYP2D6) significantly differed in the Tibetan population. Furthermore, three significant loci were related to drug response. In addition, the allele frequency of Tibetans least differed from that of East Asian populations, and most differed from that of Americans.Conclusion: Three significant loci of variation ACE rs4291, SLC19A1 rs1051296 and CYP2D6 rs1065852 were associated with drug response. This result will contribute to improving the information of the Tibetan in the pharmacogenomics database, and providing a theoretical basis for clinical individualised drug use in Tibetans.Keywords: the Tibetan population, pharmacogenomics, VIP variants